IMPACT OF SOCIALIZATION AGENTS ON BEHAVIOURAL MODIFICATION OF FEMALE BASIC SCHOOL PUPILS IN ILORIN METROPOLIS, KWARA STATE, NIGERIA - OKOJI, Olufemi Onweazu; ABDULAZEEZ, Ajoke (Ilorin Journal of Education, 2023)
Socialization as a continuous process that begins from birth to death, is a conglomeration of agents with similar norms, values and social relations within which a child’s behaviour is shaped. This study therefore examined the impact of socialization agents on behavioural modification of female basic school pupils in Ilorin Metropolis, Kwara State, Nigeria. This study was a descriptive survey type. The population for this study comprised of all female basic school pupils in Ilorin Metropolis, Kwara State, Nigeria. One hundred and ninety-three female pupils were sampled using a stratified sampling technique. Researchers’ designed questionnaire structured in a two-response-type with the reliability coefficient 0.78 was used for data collection while the data collected were analysed using descriptive statistic of percentage and inferential statistics of chi[1]square at 0.05 alpha level. Findings from this study revealed that family, school peer group and mass media had significant impact in female pupils’ behavioural modifications in Ilorin Metropolis, Nigeria. It was therefore recommended among others that parents and school teachers should establish cordial relationship with their wards and ensure that their female wards keep good company with peers.